Synthesis of Some 4‐Quinolinyl Pyridines and their Antimicrobial and Docking Studies. (3rd May 2017) - Kumar, Ramesh; Khanna, Radhika; Kumar, Parvin; Kumar, Vikas; Kamboj, Ramesh C.
Abstract : A series of some substituted diethyl 4‐(2‐chloroquinolin‐3‐yl)‐2, 6‐dimethylpyridine‐3, 5‐dicarboxylates has been synthesized from substituted diethyl4‐(2‐chloroquinolin‐3‐yl)‐1, 4‐dihydro‐2, 6‐dimethylpyridine‐3, 5‐dicarboxylates (1, 4‐DHPs) by treating the latter with SiO2 –HNO3 which proved to be a better oxidant in terms of product yield, reaction time, and cost. Further, these compounds were screened for their antimicrobial activity. All the diethyl 4‐(2‐chloroquinolin‐3‐yl)‐2, 6‐dimethylpyridine‐3, 5‐dicarboxylates exhibited more potent activities than the corresponding 1, 4‐DHPs. Further, docking simulation of the most active and least active compounds3e and2e into Escherichia coli topoisomerase II DNA Gyrase B was also performed. Abstract :